2022
DOI: 10.1111/psyg.12879
|View full text |Cite
|
Sign up to set email alerts
|

Construction of path analysis model on related factors of social isolation in older people

Abstract: Background With the gradual acceleration of population ageing, social isolation in older people has increasingly become a hot topic of social concern. The reduction of valid social participation will cause older people to weaken their sense of belonging to the community and social acquisition, negatively impacting on older people's quality of life. This study is aimed to explore the main related factors affecting the social isolation of older people, so as to provide a solid scientific basis for improving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Evidence about the relationship between depression and network scales was mixed. While Merchant et al [ 154 ] found no evidence cross-sectionally, other scholars found significant evidence that depression was associated with lower scores on network scales [ 37 , 153 , 159 ] and subscales [ 156 ]. However, the longitudinal evidence found was contradictory [ 20 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence about the relationship between depression and network scales was mixed. While Merchant et al [ 154 ] found no evidence cross-sectionally, other scholars found significant evidence that depression was associated with lower scores on network scales [ 37 , 153 , 159 ] and subscales [ 156 ]. However, the longitudinal evidence found was contradictory [ 20 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most articles followed the main-effect model [ 17 ] and considered depression as an outcome variable of social network characteristics in examining the relationship between structural social network aspects and depression among older adults. Only eight articles exclusively accounted for the reversed logic of causality: social network characteristics as an outcome of depression [ 152 159 ]. Five out of 127 articles examined the reciprocal relationship between structural social network characteristics and depression [ 19 , 20 , 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elderly people in social isolation suffer from a wide range of problems and challenges. In addition to experiencing financial difficulties (4,(23)(24)(25), they are at a greater risk of developing physical and mental health issues (26). More importantly, they have a low level of life satisfaction and a low sense of self-efficacy in changing their life conditions and perceive themselves as useless (27).…”
Section: The Life Situations Of the Elderly In Social Isolation And T...mentioning
confidence: 99%